Child well-being in Rich Countries - UNICEF Innocenti Research Centre (United Nations, 2013)
Part One of this report presents a league table of child well-being in 29 of the world's advanced economies. Part Two looks at what children say about their own well-being (including a league table of children’s life satisfaction). Part Three examines changes in child well-being in advanced economies over the first decade of the 2000s, looking at each country’s progress in educational achievement, teenage birth rates, childhood obesity levels, the prevalence of bullying, and the use of tobacco, alcohol and drugs.